Novel software tool for specifying functionality realization without physical component interaction - Li, Ye. (2008)
Many software tools have been developed to support the analysis and design of software systems. However, current analysis and design models are not able to provide integrated and precise modeling of functionality realization. This research project addresses the above-mentioned problem. It develops a novel software tool called Visual Data Flow Net.